2021
DOI: 10.1002/fsn3.2454
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of top round beef meat tenderness as a function of marinating time based on commonly evaluated parameters and regression equations

Abstract: Tenderness is greatly impacted the organoleptic and quality characteristics of meat and its products (Bojorges et al., 2020;Brito Lopes et al., 2020;Ma & Kim, 2020). Inconsistency and nonuniformly texturized meat products are the major problems encountered by the meat industry that affecting tenderness and also customer satisfaction (Stadnik & Dolatowski, 2011;Uyarcan & Kayaardi, 2019;Zhou et al., 2020). Hence, over the past few decades, the industrial sections concentrated on discovering safe and innovative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Researchers have found that acidic marinades induce marinade absorption between muscle fibers, which accelerates muscle fiber swelling [52]. On the other hand, the marination process with organic acids causes may negatively affect the color and taste value of the meat [53,54]. According to Jones et al [55], adding vinegar to beef meat products reduced the pH value from 5.64 to 4.91.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have found that acidic marinades induce marinade absorption between muscle fibers, which accelerates muscle fiber swelling [52]. On the other hand, the marination process with organic acids causes may negatively affect the color and taste value of the meat [53,54]. According to Jones et al [55], adding vinegar to beef meat products reduced the pH value from 5.64 to 4.91.…”
Section: Resultsmentioning
confidence: 99%
“…A current study by Al-Dalali et al [4] showed that with increase in marinating time found to produce more acceptable end with increase in scores in terms of sensory attributes and significant to different marinating time (p< 0.05), also increase in marinating time reduced cooking loss and shear force, indicating improved tenderness [23]. Marinating meat for an extended period, such 24 hours, can result in more tender meat with improved water retention, collagen solubility, moisture levels, and decreased effort needed for cutting [32]. This data aligns with the findings of the current investigation, which showed a notable variation in texture based on marination duration.…”
Section: Effect Of Liquid Tenderizer On Goat Meat Sensory Attributes ...mentioning
confidence: 99%
“…Meat contains collagen and protein, but acid-based marination can accelerate the process of breaking down collagen into a more soluble form, making the meat more tender. The method of marinating meat can also use acid-containing fruits such as lemon because it can break down the protein bonds of meat so that it is more tender [15]. Tender meat is more favourable than tough meat.…”
Section: Tendernessmentioning
confidence: 99%